Antiurolithiasis, Anti-Inflammatory And In Silico Docking Studies Of Karpura Shilajit - Vanukuru, N V L Suvarchala Reddy; Mudunuri, Ganga Raju; Malkapuram , Mamatha (Nepal Journal of Science and Technology, 2023)
Urolithiasis is the condition where urinary calculi are formed anywhere within the excretory organ, bladder, and/ or ureters. Asphaltum commonly called Karpura shilajit is known for different activities like antimicrobial, antidiabetic, antiulcer, fungitoxocity, estrogenic, anti-inflammatory, antihyperglycemic, antilithiatic activity and antioxidant activity. The aim of study is to evaluate anti-lithiatic activity by ethylene glycol ammonium chloride (0.75%) model for 28 days and in vitro anti-inflammatory activity by protein denaturation method using the mineral extract where cystone (500 mg/kg, p.o.) used as a standard drug in the present study. Preliminary Phytochemical screening resulted in the presence of flavonoids, saponins, carbohydrates, terpenoids and steroids. The Shilajit extract significantly restored creatinine, urea, uric acid, calcium, phosphate, oxalate, sodium and potassium levels in Ethylene glycol ammonium chloride induced urolithiasis model. Histopathological examination further confirmed the induction of lithiasis with crystal deposition in the sections of kidney treated with ethylene glycol-ammonium chloride. The mechanism by which the extract exhibited this effect is possibly through an antiinflammatory, nephroprotection. Karpura shilajit had shown significant effect on urine volume, urine pH, urine excretion, sodium and potassium levels. The steroids, terpenoids and flavonoids isolated from Gas Chromatography-Mass Spectroscopy are docked with prostaglandin synthase inhibitor for anti-inflammation activity and Glycolate oxidase / Lactate dehydrogenase inhibitor. Overall results explain us that Karpura shilajit has proven nephroprotective activity by ethylene glycol induced model along with anti-inflammatory activity i.e., by controlling renal stone formation and increasing urine flow and reduction in impaired renal tubules.